Constructionist Account Of Natural Language Communication In Aristotle’s Rhetoric - Domaradzki, Mikołaj (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2010)
While Aristotle’s metaphysics is predominantly known for its essentialism and realism, the philosopher’s rhetoric appears to challenge some of the ontological and epistemological assumptions of the fact-based approach to reality that pervade the entire Corpus Aristotelicum. The present paper Constructionist Account Of Na tural La nguage Comm unication… argues that the presence of certain “constructionist” intuitions in Aristotle’s Rhetoric results from the philosopher’s premonition that language performs various communicative functions and that, consequently, the so called “representational” can only be seen as one of them. When proposing an interpretation of those passages in which Aristotle alludes to the possibility of constructing truth and facts rather than merely presenting them, the article suggests that Aristotle’s tripartition of rhetoric be read as an anticipation of Karl Bühler’s model of language as organon, since both thinkers regard language as more than just a tool for describing reality or expressing one’s thoughts. Consequently, Aristotle’s Rhetoric departs from the ideal of truth mirroring the reality, for the philosopher is aware of the performative aspects of natural language communication.

Al igual que la metafísica aristotélica es ampliamente conocida por su esencialismo y realismo, la retórica de El Estagirita parece poner en tela de juicio ciertas suposiciones ontológicas y epistemiológicas de este enfoque hacia la realidad neutro axiológicamente que impregna el Corpus Aristotelicum entero. El presente artículo procura demostrar que la presencia de ciertas intuiciones “constructivistas” en la Retórica de Aristóteles resulta de la premonición del filósofo acerca de que la lengua desempeña varias funciones comunicativas, y la llamada “representativa” es tan solo una de ellas. Si bien en algunos fragmentos de la Retórica Aristóteles parece aludir a la posibilidad de construer la verdad y los hechos más bien frente a su mera representación, la interpretación que proponemos aquí sugiere que la tripartición aristotélica de la retórica anticipa al modelo de Karl Bühler de la lengua entendida como órganon, ya que ambos pensadores suponen que la lengua es algo más que una herramienta para describir la realidad y/o expresar sus propios pensamientos. En consecuencia, la Retórica aristotélica se aleja del ideal de la verdad como espejo de la realidad, siendo consciente, a su vez, de los aspectos performativos de la comunicación en el lenguaje natural.
Keywords: Aristotle; Rhetoric; Constructionism; Speech functions; Bühler